Management and development of oil palm cultivation in swamplands in perspective of limitation and sustainability. Issue 1 (1st May 2022) - Annisa, Wahida; Susilawati, Ani; Noor, Muhammad
Abstract: Development of oil palm plantations in swamps in the last ten years has progressed rapidly as a result of limited availability of fertile lands. Due to the nature of the environment, productivity over swamp land is quite different from other ecosystems. Studies reported that average productivity of oil palm in swamps ranges from 0.8-1.2 tons fresh fruit bunch (FFB)/ha/month (equivalently 9-10 t FFB/ha). Economic analysis shows that this productivity level does not provide a benefit to the farmers. It was reported, however, that with the intervention and introduction of good management and technology, productivity of swamp land can reach 25-27 t FFB/ha and on peat soil it can reach 19 t FFB/ha. Socio-economic factors such as capital, knowledge, technology, labor, physical infrastructure or other facilities significantly affect palm oil productivity. Identification of economic, socio-political, and ecological aspects drive a concept of sustainable development for oil palm plantation. This paper reviews results related to this development in the perspective of limiting issues related to sustainability. Development of oil palm plantations expects high productivity and stability, yet promoting equality and local wisdom towards sustainable environment. Good management of soil and water is the key for oil palm farming in swamp lands. There are four properties of sustainable agroecosystems, namely productivity, stability, sustainability and equity.